How local political economy dynamics are shaping the Belt and Road Initiative. Issue 10 (10th July 2021) - Loughlin, Neil; Grimsditch, Mark
Abstract: The Belt and Road Initiative (BRI)'s ambiguity has opened the door to varied interpretations. Developing a structural political economy analysis, we push back against overgeneralised one-directional accounts in favour of a more nuanced localised reading, to show how recipient state political economy dynamics mediate the BRI as it unfolds in participating countries. We demonstrate this through analysis of Cambodia's industrial development, drawing from evidence of special economic zones (SEZs), and specifically the Sihanoukville SEZ, now touted as a 'model' of BRI cooperation by both China and Cambodia. We show this model to be a continuation of earlier neoliberal logics of uneven growth and precarity, perpetuating Cambodia's conflictual authoritarian developmentalism. This investment, now increasingly framed under the BRI, supports infrastructure development and industrial expansion, feeding the ruling Cambodian People's Party's longstanding elite-patronage system, while generating jobs for ordinary Cambodians in manufacturing and other low-added-value industries. In our analysis, local political economy dynamics and contestation emerge as critical for explaining trajectories and outcomes associated with the BRI. In the process we unpick the discourses ascribed to the BRI in Cambodia and more broadly. Our findings have implications for policymaking in Cambodia and China, and for other development actors engaging with the BRI.